Resilience in Islamic Urban Form: Exploring Dynamics in Historic Central District of Banda Aceh, Indonesia - Senjana, Suci; Handayani, Wiwandari; Suprapti, Atik (Journal of Islamic Architecture, 2025)
Islamic cities have a distinct spatial organization and architectural character deeply influenced by Islamic principles and historical context. Therefore, examining morphology provides invaluable insights into the socio-cultural dynamics and urban form components that have shaped these cities over centuries. This research aims to distinguish the distinctive features that define Banda Aceh as an Islamic city that could influence its resilience. Moves with three objectives: to delve into the history of Islam under different rulers, map the locations of historical areas as part of the urban form components, and examine the identified components' characteristics. Drawing upon the observation, latest satellite imagery, and historical archives, the study delves into the city's urban morphology and spatial organization, facilitating a comprehensive understanding of its Islamic urban form. The findings highlight historical area typologies based on governance timelines. Key finding portrays the survival of infrastructures, including mosques, commercial areas, and public spaces, which reflect cultural practices. The growth of Banda Aceh began from the western bank of the river. It also plays a role in shaping the city layout, initially with the main role of the river as a trade transportation route in the past. Studying the resilience of urban components can enrich urban planning studies and provide inputs for policymakers that there are socio-cultural elements in the city's physical structure that have endured over time, which can support efforts to enhance resilience in the future.